Comparative Analysis of English Prepositions and Armenian Case Endings - Avetisyan, Ruzanna (Armenian Folia Anglistika, 2010)
The present article offers a comparison of the English prepositions and Armenian case endings. The examples illustrate the correspondence between different Armenian cases and English prepositions. The topic of the article is not conclusive and calls for further research since the information provided in the article can serve as solid material for further investigations of the correspondence between English prepositions and Armenian case endings. Such investigations can lead to the creation of certain grammar rules which will naturally help make the work of translation from Armenian into English and vice versa easier.